2015
DOI: 10.1002/we.1942
|View full text |Cite
|
Sign up to set email alerts
|

Variability in large‐scale wind power generation

Abstract: The paper demonstrates the characteristics of wind power variability and net load variability in multiple power systems based on real data from multiple years. Demonstrated characteristics include probability distribution for different ramp durations, seasonal and diurnal variability and low net load events. The comparison shows regions with low variability (Sweden, Spain and Germany), medium variability (Portugal, Ireland, Finland and Denmark) and regions with higher variability (Quebec, Bonneville Power Admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 11 publications
5
41
0
Order By: Relevance
“…This is less than the distance (725 km) at which Giebel found an exponential decay in the cross‐correlation of wind energy production. Kiviluoma et al also demonstrated for several power systems that the distance between wind power farms can explain the variability in wind power production.…”
Section: Resultssupporting
confidence: 61%
“…This is less than the distance (725 km) at which Giebel found an exponential decay in the cross‐correlation of wind energy production. Kiviluoma et al also demonstrated for several power systems that the distance between wind power farms can explain the variability in wind power production.…”
Section: Resultssupporting
confidence: 61%
“…The geographical distribution of installed VRE generation has a significant effect on the probability distribution of the aggregate VRE generation (Kiviluoma et al, ; Koivisto, Ekström, et al, ). In the analyzed scenarios, a notable increase in geographical distribution takes place from 2014 until 2020; however, after 2020 the overall distribution does not change significantly (Koivisto et al, ).…”
Section: Case 1: Simulating Large‐scale Wind and Solar Pv Generation mentioning
confidence: 99%
“…Providing ancillary services also from renewable power plants can contribute to an overall decrease in system costs. These achievable savings have been estimated to be in the order of a few percentages (Kiviluoma, Azevedo, Holttinen, Altiparmakis, & Cutululis, ). However, focusing on this main goal can be challenging, with involved stakeholders actively working to achieve the lowest cost (or highest ancillary service market revenue) for themselves, at a higher total cost for society.…”
Section: Discussionmentioning
confidence: 99%